Structural variation within the left globus pallidus is associated with task-switching, not stimulus updating or distractor filtering - Zacharopoulos, G; Klingberg, T; Cohen Kadosh, R (Taylor and Francis, 2020)
Cognitive control is a pivotal aspect of cognition and it is impaired in many clinical populations. To date, several distinct types of cognitive control have been proposed, and prior work demonstrated the instrumental role of basal ganglia, frontal and parietal regions. However, the role of the structural variation of these regions in cognitive control functions is poorly understood. Here, we examined in 39 adults the association between regional brain volume and three major types of cognitive control: (i) stimulus updating, (ii) task-switching, and (iii) distractor filtering. The volume of the globus pallidus was positively correlated with individual variation in task-switching , and was anatomically specific to the left hemisphere. Importantly, this region did not track performance in distractor filtering or stimulus updating. We then aimed to use transcranial direct current stimulation to target the left midline subcortical structures. However, we did not find an effect on task-switching. While the null effect in the brain stimulation prevents us from drawing causal inference from the role of globus pallidus on task-switching, our structural results reveal a novel and highly specific neurostructural mechanism for task-switching and provide a further understanding of the link between cognitive control functions and the human brain.